2019
DOI: 10.3390/scipharm87030021
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated In Silico and In Vitro Assays of Dipeptidyl Peptidase-4 and α-Glucosidase Inhibition by Stellasterol from Ganoderma australe

Abstract: Background: Ganoderma fungus is rich in terpenoids. These compounds are known for their anti-hyperglycemic activities. However, the study of terpenoids as the secondary metabolite from Ganoderma as a dipeptidyl peptidase-4 (DPP-4) inhibitor remains unexplored. In addition, we examined the α-glucosidase inhibition activity. Objective: This study aimed to isolate the major terpenoid from non-laccate Ganoderma and examined its inhibitor activity on DPP-4 and α-glucosidase enzymes, and its interaction. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…, further supports the current research work [ 48 ]. In silico studies on stellasterol isolated from Ganoderma australe highlighted the importance of hydrophobic interactions with Tyr631, Tyr662, Trp659, Tyr666, and Val711 for DPP-IV inhibition which further strengthen the current investigations [ 49 ]. Other natural compounds like malonylgenistein, Caffeic acid – 3-glucoside and Calenduloside E were proved to have interactions similar to that of CA [ 50 ].…”
Section: Discussionsupporting
confidence: 62%
“…, further supports the current research work [ 48 ]. In silico studies on stellasterol isolated from Ganoderma australe highlighted the importance of hydrophobic interactions with Tyr631, Tyr662, Trp659, Tyr666, and Val711 for DPP-IV inhibition which further strengthen the current investigations [ 49 ]. Other natural compounds like malonylgenistein, Caffeic acid – 3-glucoside and Calenduloside E were proved to have interactions similar to that of CA [ 50 ].…”
Section: Discussionsupporting
confidence: 62%
“…Doty ex Silva (Solieriaceae) and Corallopsis opuntia J. Agardh (Hypneaceae) extracts have been observed to be more effective than M. latifolia extracts (Makkar and Chakraborty 2017). All the IC 50 of the positive controls used in the study were compared with literature and the validity of the assays were supported (Mzid et al 2017;Iheagwam et al 2019aIheagwam et al , 2020Budipramana et al 2019;Sarac et al 2019). The present study showed that the isolated compounds 1-4 inhibited a-amylase and thus contributed to the a-amylase inhibition activity of the M. latifolia chloroform extract.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 kB pathway, 68 and other studies have shown that stellasterol has potential as a hypoglycemic agent. 73 In the present study, network pharmacology showed that Poria cocos may maintain internal water balance via G protein coupled receptor signaling pathways, regulating ion channel activity, and by regulating hormone levels. Furthermore, molecular docking studies involving AQP4 provided a preliminary verication of the molecular mechanisms underlying the efficacy of Poria cocos.…”
Section: Discussionmentioning
confidence: 60%